THE DIGITALIZATION OF MANDIRI SYARIAH BANK IN THE MIDDLE OF COMPETITION AND TECHNOLOGY CHANGE - Siti Bunga Fatimah; Achsania Hendratmi (Universitas Airlangga, 2020)
This study aims to analyze the BSM perspective on the phenomenon of the digital banking system in the midst of competition and technological change with the unit of analysis, namely benefits, effects, constraints, and strategies. The approach used is a qualitative approach using a single case study descriptive research method. Data collection through semi-structured interviews with informants representing BSM to describe the BSM perspective on digital banking system phenomena that occur there. In addition to BSM, researchers also interviewed other banks to increase the researchers' reports. The results of perspective research in each unit of analysis indicate that BSM behavior is less aggressive in the application of the digital banking system so as to produce a lower market reach that can reduce their competitiveness. The limitation of this research is that the researchers collected data through branch offices in Surabaya and Sidoarjo so that the data might not be able to represent other regions. However, the informant said that the implementation of the digital banking system at BSM was controlled directly by the head office, so that the management perspective at one branch office would be the same as the other branch offices.Keywords: digital banking system, Bank Syariah Mandiri (BSM), technology, digital economic society, disruptionREFFERENCE Asosiasi Penyelenggara Jasa Internet Indonesia. (2016-2019). Buletin APJII. Jakarta: APJII.ATKearney. (2014). Going digital: The banking transformation road map. Retrieved from Kearney: www.atkearney.comBadan Pusat Statistik. (2013). Proyeksi penduduk Indonesia 2010 - 2030. Jakarta: Badan Pusat Statistik.Bank Indonesia. (2010 - 2019). Islamic banking statistics. Jakarta: Bank Indonesia.Bank Syariah Mandiri. (2013). Annual report 2013 stronger fundamentals for greater Indonesia. Jakarta: PT Bank Syariah Mandiri.Bank Syariah Mandiri. (2015). Annual report 2015 semangat perubahan untuk menang. Jakarta: PT Bank Syariah Mandiri.Bank Syariah Mandiri. (2016). Annual report 2016 tumbuh berkualitas. Jakarta: PT Bank Syariah Mandiri.Bank Syariah Mandiri. (2017). Annual report 2017 tumbuh sehat berkelanjutan, mengalirkan berkah untuk negeri. Jakarta: PT Bank Syariah Mandiri.Bank Syariah Mandiri.(2018). Memperkuat daya saing melalui peningkatan keunggulan perusahaan. Jakarta: Bank Syariah Mandiri.DSN MUI. (2018, 2). Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia No:117/Dsn-Mui/Ii/2018. Retrieved From Dewan Syariah Nasional. Majelis Ulama Indonesia: http://www.dsnmui.or.idJaya, I. A. (2017). Branchless banking. Jakarta: PT Mizan Publika.King, B. (2014). Breaking bank: The innovators, rogues, and strategists rebooting banking. New Jersey: Wiley.Lembaga Penjamin Simpanan. (2012 - 2019). Distribusi simpanan bank umum. Jakarta: Lembaga Penjamin Simpanan.Malaysia: World’s Islamic Finance Marketplace. (2015). Islamic Banking. Technology and Innovation in Islamic Banking.Mckinsey & Company. (2015). Digital banking in Asia. What do consumers really want?. Australia: Mckinsey & Company.Mckinsey & Company. (2016). Unlocking Indonesia’s digital opportunity. Australia: Mckinsey & Company.Mckinsey & Company. (2018). Digital Banking. Islamic Banking in Indonesia. Australia: Mckinsey & Company.Mckinsey&Company. (2018). Global Digital. Asia’s digital banking Race: Giving customers what they want.Mckinsey & Company. (2019). Global Banking. Digital banking in Indonesia: Building loyalty and generating growth. Australia: Mckinsey & Company.OJK. (2017). Siaran pers: OJK isu panduan kantor digital, menuju perbankan digital di Indonesia. Retrieved from Otoritas Jasa Keuangan: www. ojk.go.idOJK. (2018). Digital banking technology adoption and bank efficiency: The Indonesian Case. Jakarta: Otoritas Jasa Keuangan.Otoritas Jasa Keuangan. (2014). Peraturan Otoritas Jasa Keuangan Nomor 19/POJK.13/2014 tentang layanan keuangan tanpa kantor dalam rangka keuangan inklusif. Retrieved from Otoritas Jasa Keuangan: http://www.ojk.go.idOtoritas Jasa Keuangan. (2017). Maintaining stability, increasing prosperity. Jakarta: Otoritas Jasa Keuangan.Otoritas Jasa Keuangan. (2018). Edukasi konsumen. Digital banking: nyaman dan aman harus beriringan. Jakarta: Otoritas Jasa Keuangan.Otoritas Jasa Keuangan. (2018). Peraturan Otoritas Jasa Keuangan Nomor 12 /POJK.03/2018 tentang penyelenggaraan layanan perbankan digital oleh bank umum. Retrieved from Otoritas Jasa Keuangan: http//www.ojk.go.idPerbanas. (2016). Probank: Membangun perbankan profesional. Keniscayan perbankan digital. Jakarta: Perbanas.PricewaterhouseCoopers. (2018). Digital Banking Consumer Survey. Mobile users set the agenda. USA: PricewaterhouseCoopers.PricewaterhouseCoopers. (2018). Indonesia Banking Survey. Technology shift in Indonesia is underway. Jakarta: PricewaterhouseCoopers.PricewaterhouseCoopers. (2018). State of digital. Digital transformation health check.PricewaterhouseCoopers Indonesia. (2018). PwC survey: Digital banking in Indonesia 2018. Jakarta: PricewaterhouseCoopers.Skinner, C. (2014). Digital banking strategies to launch or become a digital bank. Singapore: Marshall Cavendish Internasional (Asia) Pte Ltd.Tamrin, D. (2010). Kaidah-kaidah hukum Islam (kulliyah al-khamsah). Jakarta: UIN MALIKI PRESS.Yin, R. K. (2015). Case study research: Design and methods. California: SAGE Publications, Inc.